POLITICAL MARKETING AND COMMUNICATION STRATEGY TO WIN LEGISLATIVE NOMINEE’S COMPETITION WITHIN GOLKAR PARTY IN GENERAL ELECTION 2014 - . Pujono (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Political marketing and political communication can’t be separated when it was conceived as “product” in the marketplace. Political nominee or candidate from political parties can be perceived as product offered to consumers. Based on that premise this article to explain how politician from Golkar party at KabupatenSragen could win this competition among competitors inside party or outside parties. By focusing to those who win the competition in general election 2014 in Golkar party at KabupatenSragen, this research can expose the ways the candidate operated the political communication as political marketing. This research was a qualitative research by focusing to nominee who win the competition in Golkar party. By in depth interviewing, analyzing campaign material and programs as well as several efforts to convince the constituencies, for instances face to face communication, creating social networking, and pursuing high of acceptability, these described some of political communication strategy as political marketing to win competition in general election 2014. The result showed us that winning of competitions must integrate some ways. First, the way politician to get acceptability and positive images among constituencies. Second, involve intensely to social moment and event in society. Third, doing campaign and creating social networking. Finally, support them by giving rewards if they give their votes to candidates. The results also indicated that marketing political and political communication were intertwinted each other. One dimension support the other dimension.